2008
DOI: 10.1007/s12237-008-9126-8
|View full text |Cite|
|
Sign up to set email alerts
|

Short- and Long-Term Response of Deteriorating Brackish Marshes and Open-Water Ponds to Sediment Enhancement by Thin-Layer Dredge Disposal

Abstract: Artificial sediment enhancement using a thin layer of dredged material has been suggested as a means to increase elevation and create soil conditions conducive to increased marsh structure and function in deteriorating marshes. Using a chronosequence approach, we examined the effects of sediment enhancement in deteriorating marsh and open-water pond habitats located in six brackish marshes. Sediment enhancement of both marsh and interior pond sites had significant, immediate, and long-lasting effects on physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 34 publications
4
25
1
Order By: Relevance
“…Similarities among our references plots and published values from other brackish marshes in Louisiana (Nyman et al, 1990;DeLaune et al, 2003;La Peyre et al, 2009) suggest that brackish marsh soils in general may be highly compressible as well. Within 1 year, the surface elevation of plots that received sediment was approaching equivalency with the reference plots, and by the end of the study 889 day after sediment additions, sediment-nourished areas on average had subsided to pre-sediment surface elevations.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similarities among our references plots and published values from other brackish marshes in Louisiana (Nyman et al, 1990;DeLaune et al, 2003;La Peyre et al, 2009) suggest that brackish marsh soils in general may be highly compressible as well. Within 1 year, the surface elevation of plots that received sediment was approaching equivalency with the reference plots, and by the end of the study 889 day after sediment additions, sediment-nourished areas on average had subsided to pre-sediment surface elevations.…”
Section: Discussionsupporting
confidence: 83%
“…Although sediment-slurry application has been extensively investigated for salt marsh restoration (as cited above), a systematic and experimental evaluation of this restoration approach is lacking in lower salinity, brackish and freshwater marshes (only La Peyre et al, 2009). For instance, sediment loading on the marsh surface may cause the organic soils of brackish marshes to compress, potentially having a negative impact on elevation.…”
Section: Introductionmentioning
confidence: 99%
“…Buda Island is a general term for the geographic feature on the map that includes the Buda Backshore and Buda Lagoon salt marsh sites. This drawing was modified with the permission of Dr. Carles Alcaraz marsh accretion depends on both mineral sediment inputs from river-or wind-derived flood waters and local organic matter production from plants (La Peyre et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Coastal wetlands in the northern Gulf of Mexico region exhibit a wide range of soil organic and mineral contents (Gosselink and Hatton 1984;Nyman et al 1990;Sasser et al 1995). Wetlands in this region restored with dredged soil materials have high silt or clay content and bulk density compared to natural wetlands (Shafer and Streever 2000;Edwards and Proffitt 2003;La Peyre et al 2009). Several studies have demonstrated that growth of wetland plant species is influenced by soil characteristics (Lenssen et al 1999;Huckle et al 2000;Handley and Davy 2002;Sorrell et al 2002;Hangelbroek et al 2003;Willis and Hester 2004).…”
Section: Introductionmentioning
confidence: 99%